Pemanfaatan Aplikasi Blogger Sebagai Media Promosi Jasa Dekorasi Pernikahan Pada Rahma Pelaminan - Zahara Odelia; Nova Dilastri; Soelarno Soelarno (CV. ITTC INDONESIA, 2025)
The purpose of this study is to provide an understanding of the use of Blogger as a digital promotional tool for the wedding decoration service business